2017
DOI: 10.1016/j.jconrel.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up synthesis of carbon nanoparticles with higher doxorubicin efficacy

Abstract: Nanomedicine requires intelligent and non-toxic nanomaterials for real clinical applications. Carbon materials possess interesting properties but with some limitations due to toxic effects. Interest in carbon nanoparticles (CNPs) is increasing because they are considered green materials with tunable optical properties, overcoming the problem of toxicity associated with quantum dots or nanocrystals, and can be utilized as smart drug delivery systems. Using black tea as a raw material, we synthesized CNPs with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 81 publications
3
47
0
Order By: Relevance
“…The mean body weight ( Figure 6B) and blood cells (Figure 6C) of the HCS-injected Balb/c mice were similar to those of the control mice (Balb/c mice without HCS administration). This result was in accordance with the results reported by Bayda et al 37 …”
Section: Ex Vivo and In Vivo Toxicity Assayssupporting
confidence: 94%
See 1 more Smart Citation
“…The mean body weight ( Figure 6B) and blood cells (Figure 6C) of the HCS-injected Balb/c mice were similar to those of the control mice (Balb/c mice without HCS administration). This result was in accordance with the results reported by Bayda et al 37 …”
Section: Ex Vivo and In Vivo Toxicity Assayssupporting
confidence: 94%
“…The results revealed that Dox release was comparatively slower at alkaline pH (pH 7.4) as shown in Figure 7C (*p,0.05; **p,0.01). This observation was consistent with the observations reported by Bayda et al 37 and Qiu et al 42 Dox is a weak amphipathic base. The protonated form of Dox is ~10-fold that of free base.…”
supporting
confidence: 93%
“…Organoids were phenotypically characterized by histological and immunohistochemical (IHC) staining for the most common liver markers ( Figure 2). In accordance with cyto-morphological evidence reported in the literature [19], microscopic examination of haematoxylin and eosin (H&E) staining showed that liver organoids had the typical features of hepatic progenitors and mature hepatocytes. Liver organoids retained their stemness and proliferative potential, confirmed respectively by the strong immunopositivity for CD133 and octamer-binding transcription factor 4 (OCT4) stem cell markers and Ki67 proliferation marker.…”
Section: Liver Organoid Toxicitysupporting
confidence: 86%
“…DOX can also directly loaded on the surface of CDs for localized cancer therapy by simply mixing these CDs and DOX [127,128]. DOX can be released in the tumor acid microenvironment [129,130]. Chemotherapeutic DNA-modifying cisplatin and topoisomerase II-inhibiting DOX were conjugated on the full-color emissive CDs via a pH sensitive hydrazone bond [131].…”
Section: Fluorescent Cds Conjugated With Chemical Therapeutic Agentsmentioning
confidence: 99%